Composition operator induced by ?(z) = sz + t for which |s|?1, |t|<1 and |s|+|t|?1 - Baghdad Science Journal (مجلة بغداد للعلوم)
We study in this paper the composition operator that is induced by ?(z) = sz + t. We give a characterization of the adjoint of composiotion operators generated by self-maps of the unit ball of form ?(z) = sz + t for which |s|?1, |t|